Betula mcallisteri sp. nov. (sect. Acuminatae, Betulaceae), a new diploid species overlooked in the wild and in cultivation, and its relation to the widespread B. luminifera - Zhang, Huayu; Ding, Junyi; Holstein, Norbert; Wang, Nian (Frontiers in Plant Science, 2023)
Taxa are traditionally identified using morphological proxies for groups of evolutionarily isolated populations. These proxies a commonly characters deemed by taxonomists as significant. However, there is no general rule which character or sets of characters are appropriate to circumscribe taxa, leading to discussions and uncertainty. Birch species are notoriously hard to identify due to strong morphological variability and factors such as hybridization and the existence of several ploidy levels. Here, we present evidence for an evolutionarily isolated line of birches from China that are not distinguishable by traditionally assumed taxon recognition proxies, such as fruit or leaf characters. We discovered that some wild material in China and some cultivated in the Royal Botanic Gardens Edinburgh, formerly recognized as Betula luminifera, differed from other individuals by having a peeling bark and a lack of cambial fragrance. We use restriction site-associated DNA sequencing and flow cytometry to study the evolutionary status of the unidentified Betula samples to assess the extent of hybridization between the unidentified Betula samples and typical B. luminifera in natural populations. Molecular analyses show the unidentified Betula samples as a distinct lineage and reveal very little genetic admixture between the unidentified samples and B. luminifera. This may also be facilitated by the finding that B. luminifera is tetraploid, while the unidentified samples turned out to be diploid. We therefore conclude that the samples represent a yet unrecognized species, which is here described as Betula mcallisteri.